0.6x+14.1=x-7.3

Simple and best practice solution for 0.6x+14.1=x-7.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6x+14.1=x-7.3 equation:


Simplifying
0.6x + 14.1 = x + -7.3

Reorder the terms:
14.1 + 0.6x = x + -7.3

Reorder the terms:
14.1 + 0.6x = -7.3 + x

Solving
14.1 + 0.6x = -7.3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
14.1 + 0.6x + -1x = -7.3 + x + -1x

Combine like terms: 0.6x + -1x = -0.4x
14.1 + -0.4x = -7.3 + x + -1x

Combine like terms: x + -1x = 0
14.1 + -0.4x = -7.3 + 0
14.1 + -0.4x = -7.3

Add '-14.1' to each side of the equation.
14.1 + -14.1 + -0.4x = -7.3 + -14.1

Combine like terms: 14.1 + -14.1 = 0.0
0.0 + -0.4x = -7.3 + -14.1
-0.4x = -7.3 + -14.1

Combine like terms: -7.3 + -14.1 = -21.4
-0.4x = -21.4

Divide each side by '-0.4'.
x = 53.5

Simplifying
x = 53.5

See similar equations:

| 3x(4/2) | | 3(8x+9)-9x=7x+19 | | Y-0=1/4[x-(-4)] | | 14-2(3a+1)=2(3a-2) | | 7(5cx+y)=34cx-8y | | 3(4x-1.3)=5x-3.9 | | 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 | | Y=4+3(0) | | 5t-13-8t=-20-33t-5 | | 5+3=y | | 6x+8=8x+11 | | 10x-7=5x-5 | | (1/2)x=8 | | (8x)=(2x+23) | | 5-2n=8n-(-4n) | | 5x-2x+21= | | (X)=(3x-10) | | X+X+25=75 | | 64=3x^2 | | 500x-0.69=700x+0.29 | | 8x/3-x=x/6-7/2 | | Y=4+3(-4) | | -6.4=128.0 | | 12x+2y=-48 | | 3.1x-37=2.1x+8 |

Equations solver categories